SoxD proteins influence multiple stages of oligodendrocyte development and modulate SoxE protein function. - Sock, Elisabeth; Wegner, Michael; Stolt, Claus; et al. (Developmental Cell, 2006)
The myelin-forming oligodendrocytes are an excellent model to study transcriptional regulation of specification events, lineage progression, and terminal differentiation in the central nervous system. Here, we show that the group D Sox transcription factors Sox5 and Sox6 jointly and cell-autonomously regulate several stages of oligodendrocyte development in the mouse spinal cord. They repress specification and terminal differentiation and influence migration patterns. As a consequence, oligodendrocyte precursors and terminally differentiating oligodendrocytes appear precociously in spinal cords deficient for both Sox proteins. Sox5 and Sox6 have opposite functions than the group E Sox proteins Sox9 and Sox10, which promote oligodendrocyte specification and terminal differentiation. Both genetic as well as molecular evidence suggests that Sox5 and Sox6 directly interfere with the function of group E Sox proteins. Our studies reveal a complex regulatory network between different groups of Sox proteins that is essential for proper progression of oligodendrocyte development. © 2006 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.med.IB.LPCIPDBI.soxdpr
Keywords: DEVBIO